2007
DOI: 10.1097/mao.0b013e31802bea4b
|View full text |Cite
|
Sign up to set email alerts
|

Aggressiveness in Cholesterol Granuloma of the Temporal Bone May Be Determined by the Vigor of Its Blood Source

Abstract: These observations lend further support to the theory that aggressiveness of CG is sustained by a robust source of ongoing hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 7 publications
0
31
0
Order By: Relevance
“…The authors state that the 'obstruction-vacuum' hypothesis does not account for a source of hemorrhage significant enough to produce such aggressive cholesterol granulomas. Rather, a highly vascular marrow cavity (such as the marrow in the petroclival junction of the petrous apex) would provide the necessary amount of ongoing hemorrhage required to produce the aggressive cholesterol granulomas seen in the petrous apex [10 ].…”
Section: Pathogenesismentioning
confidence: 99%
“…The authors state that the 'obstruction-vacuum' hypothesis does not account for a source of hemorrhage significant enough to produce such aggressive cholesterol granulomas. Rather, a highly vascular marrow cavity (such as the marrow in the petroclival junction of the petrous apex) would provide the necessary amount of ongoing hemorrhage required to produce the aggressive cholesterol granulomas seen in the petrous apex [10 ].…”
Section: Pathogenesismentioning
confidence: 99%
“…A case series by Pfister et al (4) implicated rich sources of hemorrhage as contributors to the progression of atypically aggressive CGs. To our knowledge, the present case represents the first in the literature to show a non-CG petrous apex with a pronounced air-marrow interface later developing an ipsilateral cholesterol granuloma in a single patient.…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol crystals that result from both breakdown of these lipids within the marrow instigate an inflammatory reaction that is believed to be necessary for formation of these cysts (1,11). Some have suggested that the variability in aggressiveness of the cholesterol granuloma is related to the richness of the adjacent blood supply (12). The end result of this process is demonstrated in Figure 7, where clefts left from dissolved cholesterol crystals are present in the remaining fluid as well as surrounding granulomatous reaction with foreign body giant cells present.…”
Section: Discussionmentioning
confidence: 99%